La investigación como proceso clave para la planificación estratégica del marketing - Valdivieso, Alexandra (2021)
Currently in business world, information has become one of the most valuable intangible assets for companies, since it allows us to understand the past, analyze the present and predict the future of organizations. In that way, research processes focused on collecting and analyzing information to generate knowledge about offer and demand are necessary for the success of business strategies. Decisions supported by reliable information can achieve better results for companies, as well as control and reduce market risks, while the lack of and efficient management of information can lead to economic losses and positioning among the target audience. This is how market research has a important role for strategic business management. This article provides a brief introduction to market research, based on the analysis of different market research methods applied to success and failure cases of recognized organizations.